2004
DOI: 10.1021/np049751v
|View full text |Cite
|
Sign up to set email alerts
|

Vittatalactone, a β-Lactone from the Striped Cucumber Beetle, Acalymma vittatum

Abstract: A novel beta-lactone, vittatalactone (1), was isolated from collections of airborne volatile compounds from feeding male striped cucumber beetles, Acalymma vittatum. The structure of 1 was determined to be (3R,4R)-3-methyl-4-(1,3,5,7-tetramethyloctyl)oxetan-2-one by microderivatization, GC-MS, and NMR studies. The absolute configurations at C-2 and C-3 on the beta-lactone ring were assigned by use of the modified Mosher method, applied to the beta-hydroxy acid methyl ester resulting from methanolysis of 1. Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Actually, we had to decide between 4 structures: syn , syn -, syn , anti -, anti , syn -, and anti , anti -configuration of the methyl groups at carbons 6, 8, and 10. Since semiochemicals representing saturated polydeoxypropionates typically show syn -configuration, suggesting general principles in enzymatic chain elongation [16,18], we hypothesized (2 E ,4 E ,6 S ,8 S ,10 S )-tetramethyltrideca-2,4-diene or its enantiomer to be the natural product.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, we had to decide between 4 structures: syn , syn -, syn , anti -, anti , syn -, and anti , anti -configuration of the methyl groups at carbons 6, 8, and 10. Since semiochemicals representing saturated polydeoxypropionates typically show syn -configuration, suggesting general principles in enzymatic chain elongation [16,18], we hypothesized (2 E ,4 E ,6 S ,8 S ,10 S )-tetramethyltrideca-2,4-diene or its enantiomer to be the natural product.…”
Section: Resultsmentioning
confidence: 99%
“…Vittatalactone (9) and its minor nor-derivative 16 have been isolated from the striped cucumber beetle, Acalymma vittatum (Coleoptera: Chrysomelidae). 7 These male specic compounds show electrophysiological activity in antennae of both sexes, and were suggested to act as an aggregation pheromone, 7,8 but no behavioural studies have been reported. The absolute conguration shown has been deduced by total synthesis of the enantiomers.…”
Section: Small Ring Lactonesmentioning
confidence: 99%
“…353 Acalymma vittatum can be synthesized in a short sequence employing two Ircatalyzed diastereoselective hydrogenations. 354 The latter was converted into corresponding hydroxy ester through transesterification with NaOMe and further converted into iodide 253 (Scheme 29.32).…”
Section: Ir-catalyzed Hydrogenation In Stereoselective Synthesesmentioning
confidence: 99%